Skills and Youth Entrepreneurship in Africa: Analysis with Evidence from Swaziland - Zuzana Brixiova; Mthuli Ncube; Zorobabel Bicaba (Institute for the Study of Labor (IZA), 2014)
The shortages of entrepreneurial skills have lowered search effectiveness of potential young entrepreneurs and the rate of youth start-ups. Our paper contributes to closing a gap in the entrepreneurship and development literature with a model of costly firm creation and skill differences between young and adult entrepreneurs. The model shows that for young entrepreneurs facing high costs of searching for business opportunities, support for training is more effective in stimulating productive start-ups than subsidies. The case for interventions targeted at youth rises in societies with high costs of youth unemployment. We test the role of skills and training for productive youth entrepreneurship on data from a recent survey of entrepreneurs in Swaziland.
Keywords: J11; J08; L26; O11; 330; youth entrepreneurship; model of skills and structural transformation; policies; Africa